Pituitary cells in man during aging: An immunohistological and morphometric study - Čukuranović-Kokoris Jovana; Kundalić Braca; Pavlović Miljana; Ugrenović Sladjana (Journal of Medical Biochemistry)
Background: Aging is a multifactorial process, which inevitably leads to numerous changes in the life of each individual. As the lifespan of people around the world has increased, scientists began to study the mechanisms that would enable high-quality and safe aging. In this review, the focus is on showing the effect of aging on the characteristics of pituitary cells. Methods: In order to write this review, we undertook an electronic literature search through the PubMed and Google Scholar databases using the terms aging, histological, ultrastructure of pituitary cells, also using the "related articles" option. We also analyzed authored and co-authored articles, which were necessary for this type of publication. Results: This review article describes the immuno-histological, ultrastructural and morphometric characteristics of adrenocorticotropic (ACTH), somatotropic (GH), gonadotropic (LH) and folliculostellate (FS) pituitary cells during aging, in young (about 47 years) and old (over 70 years) human cadavers. Conclusions: The described immunohistological and morphometric characteristics of pituitary cells in this review showed that the volume density of ACTH, GH and LH cells was statistically increased (p<0.05) in old cadavers, which indicates an attempt by these cells to bring the pituitary gland to a relatively balanced state.